Digital Media Tools to Increase Virtual Da'wah of Muhammadiyah Mosque at Pimpinan Cabang Muhammadiyah Gombong - Irmawan Andri Nugroho; Fajar Agung Nugroho; Citra Ayu Salma Fuaida; Ahmad Anwar Rosyidi; Syahrul Gunawan; Muhtadi Nur Muhammadi (Urecol Journal. Part F: Community Development, 2022)
Covid-19 pandemic requires us to reduce crowds like dakwah activities in mosques. If this continues for a long time, it is feared that the community will receive less spiritual care and will be further away from religious teachings. Virtual da'wah is an alternative in the digital era. The use of social media for virtual dakwah can then be an effective da'wah media if it is designed creatively. The target of this activity is the mosques takmir at PCM Gombong. The activity begins with the preparation stage, continues with the implementation, and ends with the evaluation and reporting of activities. The training provided is in the form of using various digital media and video conferencing which can be used as virtual da'wah media. In practice, the team serves as a facilitator and presents presenters and oversees the course of the activity from start to finish. PCM Gombong as a partner is authorized to help coordinate activities and provide the necessary facilities. This activity is carried out using a hybrid method. There are 11 Participants who oined in this activity from various delegates at PCM Gombong. During the Covid-19 pandemic, activities were carried out by educations, simulations, and discussions in accordance with health protocols to prevent transmission of the virus that causes Covid-19. After the education was carried out, it was found that there was an increase in the ability of participants to create flyer designs and other interesting content uploaded on social media.